Nonalcoholic Steatohepatitis in a Patient with Ataxia-Telangiectasia. (6th January 2014) - Caballero, Trinidad; Caba-Molina, Mercedes; Salmerón, Javier; Gómez-Morales, Mercedes
Abstract : Ataxia-telangiectasia (A-T) is a rare disease characterized by neurodegenerative alterations, telangiectasia, primary immunodeficiency, extreme sensitivity to radiation, and susceptibility to neoplasms. A-T patients have inactivation of ataxia-telangiectasia-mutated (ATM) protein, which controls DNA double-strand break repair and is involved in oxidative stress response, among other functions; dysfunctional control of reactive oxygen species may be responsible for many of the clinical manifestations of this disease. To the best of our knowledge, hepatic lesions of steatohepatitis have not previously been reported in A-T patients. The present study reports the case of a 22-year-old man diagnosed with A-T at the age of 6 years who was referred to our Digestive Disease Unit with a three-year history of hyperlipidemia and liver test alterations. Core liver biopsy showed similar lesions to those observed in nonalcoholic steatohepatitis. Immunohistochemical staining disclosed the absence of ATM protein in hepatocyte nuclei. We suggest that the liver injury may be mainly attributable to the oxidative stress associated with ATM protein deficiency, although other factors may have made a contribution. We propose the inclusion of A-T among the causes of nonalcoholic steatohepatitis, which may respond to antioxidant therapy.